2015
DOI: 10.1039/c5ib00080g
|View full text |Cite
|
Sign up to set email alerts
|

Single molecular force across single integrins dictates cell spreading

Abstract: Cells’ ability to sense and interpret mechanical signals from the extracellular milieu modulates the degree of cell spreading. Yet how cells detect such signals and activate downstream signaling at the molecular level remain elusive. Herein, we utilize tension gauge tether (TGT) platform to investigate underlying molecular mechanism of cell spreading. Our data from both differentiated cells of cancerous and non-cancerous origin show that for the same stiff underlying glass substrates and for same ligand densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 39 publications
(77 reference statements)
3
54
1
Order By: Relevance
“…T tol values can thus be tuned monotonically as a function of the distance between the biotin and the integrin ligand (Fig. 1a) [11,12,15]. Glass surfaces were passivated with biotinylated bovine serum albumin (BSA) prior to coating with neutravidin [12,16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T tol values can thus be tuned monotonically as a function of the distance between the biotin and the integrin ligand (Fig. 1a) [11,12,15]. Glass surfaces were passivated with biotinylated bovine serum albumin (BSA) prior to coating with neutravidin [12,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Tension gauge tethers of different tension tolerance were immobilized on passivated glass bottom dishes at a cyclic-RGDfK ligand density of ~ 600 ligands/μm 2 (one ligand in every 40 nm) as described elsewhere [11,12]. An earlier study showed that cell spreading and FA formations are not supported when the spacing between integrin binding sites is more than 58 nm [13].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, cells adhered stably if TGT with T tol ≥ 43 pN was used. The tension threshold appeared universal across several different cell types, both cancerous and noncancerous [32,34], and was shown to hold as early as the first 5 minutes of adding the cells to the TGT-coated surface [32]. This 40 pN force across a single bond outside the cell may contribute to the range of single molecule forces, 5 pN-25 pN, proposed to be experienced by the intracellular proteins that bridge integrins to the actin cytoskeleton [11,17,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…This number is estimated from the known surface density given 1 μM incubation concentrations (about 400 TGT=μm 2 ) [34] and the measured average area of cells attached to the strong TGT and MP spots (about 600 μm 2 ). For a point of reference, the aerial footprint of CHO-K1 cells used in our experiments ranges from 80 μm 2 (for the cells that do not adhere to the surface with weak tethers and just leave a fluorescent footprint) to 800 μm 2 (for the cells adhered to the surface with strong tethers).…”
Section: Multiplexing Leads To Ultrasensitivity For Strong Tgtmentioning
confidence: 99%
See 1 more Smart Citation